Processing math: 100%

Solution Manual of "Elementary Linear Algebra": 2. Matrices (Part-1)

This document is the solution manual of “Elementary Linear Algebra” which was written by K. R. Matthews, University of Queensland.
The free printable PDF format lecture can be Downloaded Here


Summary
  • Matrix
    A matrix over a field F is a rectangular array of elements from F. The symbol M_{m\times n}(F) denotes the collection of all m\times n matrices over F.
    Matrices will usually be denoted by capital letters and the equation A=[a_{ij}] means that the element in the i-th row and j-th column of the matrix A equals a_{ij}.
  • Equality of matrices
    Matrices A, B are said to be equal if A and B have the same size and corresponding elements are equal; i.e. A and B \in M_{m\times n}(F) and A=[a_{ij}], B=[b_{ij}], with a_{ij}=b_{ij} for 1\leq i\leq m, 1\leq j\leq n.
  • Addition (subtraction) of matrices
    Let A=[a_{ij}] and B=[b_{ij}] be of the same size. Then A\pm B is the matrix obtained by adding (subtracting) corresponding elements of A and B; that is A\pm B=[a_{ij}]\pm[b_{ij}]=[a_{ij}\pm b_{ij}].
  • Scalar multiple of a matrix
    Let A=[a_{ij}] and t\in F (t is a scalar). Then tA is the matrix obtained by multiplying all elements of A by t; that is tA=t[a_{ij}]=[ta_{ij}].
  • Additive inverse of a matrix
    Let A=[a_{ij}]. Then -A is the matrix obtained by replacing the elements of A by their additive inverses; that is -A=-[a_{ij}]=[-a_{ij}].
  • The zero matrix
    For each m, n the matrix in M_{m\times n}(F), all of whose elements are zero, is called the zero matrix (of size m\times n) and is denoted by the symbol 0.
  • Matrix product
    • Definition
      Let A=[a_{ij}] be a matrix of size m\times n and B=[b_{jk}] be a matrix of size n\times p; that is the number of columns of A equals the number of rows of B. Then AB is the m\times p matrix C=[c_{ik}] whose (i, k)-th element is defined by the formula c_{ik}=\sum_{j=1}^{n}a_{ij}b_{jk}=a_{i1}b_{1k} +\cdots+a_{in}b_{nk}.
    • Basic laws
      (AB)C=A(BC) t(AB)=(tA)B=A(tB) (A+B)C=AC+BC D(A+B)=DA+DB where the size of A, B, C, D should satisfy the definition of matrix product, and t is a scalar in the field F.
  • The identity matrix
    The n\times n matrix I_n=[\delta_{ij}], defined by \delta_{ij}=1 if i=j, \delta_{ij}=0 if i\neq j, is called the n\times n identity matrix of order n. For example, I_2=\begin{bmatrix}1&0\\0&1 \end{bmatrix}.
    If A is m\times n, then I_mA=A=AI_n.
  • k-th power of a matrix
    If A is an n\times n matrix, A^k is defined recursively as follows: A_0=I_n, and A^{k+1}=A^kA for k\geq0. For example, A^1=A^0A=I_nA=A and A^2=A^1A=AA.
  • Mathematical Induction
    If P_n denotes a mathematical statement for each n\geq1, satisfying
    (1) P_1 is true,
    (2) the truth of P_n implies that of P_{n+1} for each n\geq1,
    then P_n is true for all n\geq1.

Problems 2.4

1. Let A, B, C, D be matrices defined by A=\begin{bmatrix}3 & 0\\ -1 & 2\\ 1 & 1\end{bmatrix}, \, B=\begin{bmatrix}1& 5& 2\\-1& 1& 0\\ -4& 1& 3 \end{bmatrix},\, C=\begin{bmatrix}-3& -1\\ 2& 1\\ 4& 3 \end{bmatrix}, \, D=\begin{bmatrix}4& -1\\ 2& 0 \end{bmatrix}. Which of the following matrices are defined? Compute those matrices which are defined. A+B,\ A+C,\ AB,\ BA,\ CD,\ DC,\ D^2.
Solution:
A+C=\begin{bmatrix}3-3& 0-1\\-1+2& 2+1\\ 1+4& 1+3 \end{bmatrix}=\begin{bmatrix}0& -1\\1& 3\\ 5& 4 \end{bmatrix}
BA=\begin{bmatrix}1\times3-5\times1+2\times1& 1\times0+5\times2+2\times1\\-1\times3-1\times1+0\times1& -1\times0+1\times2+0\times1\\ -4\times3-1\times1+3\times1&-4\times0+1\times2+3\times1 \end{bmatrix}=\begin{bmatrix}0 &12\\-4&2\\-10&5 \end{bmatrix} CD=\begin{bmatrix}-14 &3\\10& -2\\22& -4 \end{bmatrix} D^2=\begin{bmatrix}14& -4\\8& -2 \end{bmatrix}
2. Let A=\begin{bmatrix}-1& 0& 1\\ 0& 1& 1 \end{bmatrix}. Show that if B is a 3\times2 such that AB=I_2, then B=\begin{bmatrix}a& b\\ -a-1& 1-b\\a+1& b \end{bmatrix} for suitable numbers a and b. Use the associative law to show that (BA)^2B=B.

Solution:
Let B=\begin{bmatrix}a& b\\c& d\\e& f \end{bmatrix}, and we have AB=\begin{bmatrix}-1& 0& 1\\ 0& 1& 1 \end{bmatrix}\cdot\begin{bmatrix}a& b\\c& d\\e& f \end{bmatrix}=\begin{bmatrix}-a+e &-b+f\\c+e&d+f \end{bmatrix}=I_2=\begin{bmatrix}1& 0\\ 0& 1 \end{bmatrix} Thus \begin{cases}-a+e=1\\-b+f=0\\c+e=0\\d+f=1 \end{cases}\Rightarrow\begin{cases}c=-e=-(a+1)=-a-1\\ d=1-f=1-b\\e=a+1\\f=b \end{cases} That is B=\begin{bmatrix}a& b\\ -a-1& 1-b\\a+1& b \end{bmatrix} Next (BA)^2B=BA\cdot BA\cdot B=B\cdot(AB)\cdot(AB)=B\cdot I_2\cdot I_2=B\cdot I_2=B
3. If A=\begin{bmatrix}a& b\\c& d \end{bmatrix}, prove that A^2-(a+d)A+(ad-bc)I_2=0

Solution:
Since
A^2=\begin{bmatrix}a& b\\c& d \end{bmatrix}\cdot\begin{bmatrix}a& b\\c& d \end{bmatrix}=\begin{bmatrix}a^2+bc& ab+bd\\ac+cd& bc+d^2 \end{bmatrix} (a+d)\cdot A=\begin{bmatrix}a^2+ad& ab+bd\\ac+cd& ad+d^2 \end{bmatrix} (ad-bc)I_2=(ad-bc)\cdot\begin{bmatrix}1& 0\\ 0& 1 \end{bmatrix}=\begin{bmatrix}ad-bc& 0\\ 0& ad-bc \end{bmatrix} Thus A^2-(a+d)A+(ad-bc)I_2 =\begin{bmatrix}a^2+bc& ab+bd\\ac+cd& bc+d^2 \end{bmatrix}- \begin{bmatrix}a^2+ad& ab+bd\\ac+cd& ad+d^2 \end{bmatrix} +\begin{bmatrix}ad-bc& 0\\ 0& ad-bc \end{bmatrix} =\begin{bmatrix}0& 0\\0& 0 \end{bmatrix}=0
4. If A=\begin{bmatrix}4& -3\\ 1& 0 \end{bmatrix}, use the fact A^2=4A-3I_2 and the mathematical induction, to prove that A^n={3^n-1\over2}A+{3-3^n\over2}I_2,\ \text{if}\ n\geq1.
Solution:
Note that according to the previous problem we have a=4,\ b=-3,\ c=1,\ d=0 in this problem, and hence we have A^2-4A+3I_2=0 which provided by the condition. By using mathematical induction, we have P_1: A^1={3-1\over2}A+{3-3\over2}I_2=A is true; And suppose P_n: A^n={3^n-1\over2}A+{3-3^n\over2}I_2 is true, then we have P_{n+1}: A^{n+1}=A\cdot A^n={3^n-1\over2}A^2+{3-3^n\over2}AI_2 ={3^n-1\over2}\cdot(4A-3I_2)+{3-3^n\over2}A ={4\cdot3^n-4+3-3^n\over2}A- {3^{n+1}-3\over2}I_2 ={3^{n+1}-1\over2}A+{3-3^{n+1}\over2}I_2 which is true. Thus the original assumption P_n is true.

5. A sequence of numbers x_1,\ x_2,\ \cdots,\ x_n,\ \cdots satisfies the recurrence relation x_{n+1}=ax_n+bx_{n-1} for n\geq1, where a and b are constant. Prove that \begin{bmatrix}x_{n+1}\\ x_n \end{bmatrix}=A\begin{bmatrix}x_n\\ x_{n-1} \end{bmatrix}, where A=\begin{bmatrix}a& b\\1& 0 \end{bmatrix} and hence express \begin{bmatrix}x_{n+1}\\x_n \end{bmatrix} in terms of \begin{bmatrix}x_1\\x_0 \end{bmatrix}.
If a=4 and b=-3, use the previous question to find a formula for x_n in terms of x_1 and x_0.

Solution:
It is easy to see that A\begin{bmatrix}x_n\\ x_{n-1} \end{bmatrix}=\begin{bmatrix}a& b\\1& 0 \end{bmatrix}\cdot\begin{bmatrix}x_n\\ x_{n-1} \end{bmatrix}=\begin{bmatrix}ax_n+bx_{n-1}\\x_n \end{bmatrix}=\begin{bmatrix}x_{n+1}\\ x_n \end{bmatrix} By recurrence relation we have \begin{bmatrix}x_{n+1}\\ x_n \end{bmatrix}=A\begin{bmatrix}x_n\\ x_{n-1} \end{bmatrix}=A\cdot A\begin{bmatrix}x_{n-1}\\ x_{n-2} \end{bmatrix}=A^2\begin{bmatrix}x_{n-1}\\ x_{n-2} \end{bmatrix}=\cdots=A^n\begin{bmatrix}x_{1}\\ x_{0} \end{bmatrix} When a=4 and b=-3, A=\begin{bmatrix}4& -3\\1& 0 \end{bmatrix}, and according to the previous results we have \begin{bmatrix}x_{n+1}\\ x_n \end{bmatrix}=A^n\begin{bmatrix}x_{1}\\ x_{0} \end{bmatrix} =\left({3^n-1\over2}A+{3-3^n\over2}I_2\right)\cdot\begin{bmatrix}x_{1}\\ x_{0} \end{bmatrix} =\left({3^n-1\over2}\cdot\begin{bmatrix}4& -3\\1& 0 \end{bmatrix}+{3-3^n\over2}\cdot\begin{bmatrix}1& 0\\ 0& 1 \end{bmatrix}\right)\cdot\begin{bmatrix}x_{1}\\ x_{0} \end{bmatrix} =\begin{bmatrix}2\cdot(3^n-1)+{3-3^n\over2}&-{3\over2}\cdot (3^n-1)\\ {3^n-1\over2}&{3-3^n\over2}\end{bmatrix}\cdot\begin{bmatrix}x_{1}\\ x_{0} \end{bmatrix} Thus we only need to compute the entry of (2, 1) which is x_n: x_n={3^n-1\over2}x_1+{3-3^n\over2}x_0.
6. Let A=\begin{bmatrix}2a&-a^2\\1&0 \end{bmatrix}.
(a) Prove that A^n=\begin{bmatrix}(n+1)a^n&-na^{n+1}\\na^{n-1} & (1-n)a^n \end{bmatrix},\ \text{if}\ n\geq1.
(b) A sequence x_0,\ x_1,\ \cdots,\ x_n,\ \cdots satisfies x_{n+1}=2ax_n-a^2x_{n-1} for n\geq1. Use part (a) and the previous question to prove that x_n=na^{n-1}x_1+(1-n)a^nx_0 for n\geq1.

Solution:
(a) Using mathematical induction: P_1: A^1=\begin{bmatrix}(1+1)a&-a^2\\1&0 \end{bmatrix}=A is true; Suppose that P_n: A^n=\begin{bmatrix}(n+1)a^n&-na^{n+1}\\na^{n-1} & (1-n)a^n \end{bmatrix} is true, and we have P_{n+1}: A^{n+1}=A\cdot A^n=\begin{bmatrix}2a&-a^2\\1&0 \end{bmatrix}\cdot\begin{bmatrix}(n+1)a^n&-na^{n+1}\\na^{n-1} & (1-n)a^n \end{bmatrix} =\begin{bmatrix}(2n+2)a^{n+1}-na^{n+1}&-2na^{n+2}-(1-n)a^{n+2}\\(n+1)a^{n} & -na^{n+1} \end{bmatrix} =\begin{bmatrix}(n+2)a^{n+1}&-(n+1)a^{n+2}\\(n+1)a^{n} & -na^{n+1} \end{bmatrix} follows the form of A^{n}, and hence the original assumption P_n is true.

(b) Since x_{n+1}=2ax_n-a^2x_{n-1}, we have \begin{bmatrix}x_{n+1}\\x_n \end{bmatrix}=\begin{bmatrix}2a&-a^2\\1&0\end{bmatrix}\cdot\begin{bmatrix}x_n\\x_{n-1} \end{bmatrix} = A^{n}\cdot\begin{bmatrix}x_1\\x_0 \end{bmatrix} =\begin{bmatrix}(n+1)a^n&-na^{n+1}\\na^{n-1} & (1-n)a^n \end{bmatrix}\cdot\begin{bmatrix}x_1\\x_0 \end{bmatrix} Thus the entry of (2, 1) is x_n: x_n=na^{n-1}x_1+(1-n)a^nx_0.
7. Let A=\begin{bmatrix}a&b\\c&d \end{bmatrix} and suppose that \lambda_1 and \lambda_2 are the roots of the quadratic polynomial x^2-(a+d)x+(ad-bc). (\lambda_1 and \lambda_2 may be equal.)
Let k_n be defined by k_0=0, k_1=1 and for n\geq2 k_n=\sum_{i=1}^{n}\lambda_1^{n-i}\lambda_2^{i-1}. Prove that k_{n+1}=(\lambda_1+\lambda_2)k_n-\lambda_1\lambda_2k_{n-1}, if n\geq1. Also prove that k_n=\begin{cases}\displaystyle{(\lambda_1^{n}-\lambda_2^{n}) \over (\lambda_1-\lambda_2)}& \mbox{if} \lambda_1\neq\lambda_2,\\ n\lambda_1^{n-1} & \mbox{if} \lambda_1=\lambda_2.\end{cases} Use mathematical induction to prove that if n\geq1, A^n=k_nA-\lambda_1\lambda_2k_{n-1}I_2.
Solution:
First, we prove k_{n+1}=(\lambda_1+\lambda_2)k_n-\lambda_1\lambda_2k_{n-1}.
(\lambda_1+\lambda_2)k_n-\lambda_1\lambda_2k_{n-1} =(\lambda_1+\lambda_2(\lambda_1^{n-1}+\lambda_1^{n-2} \lambda_2 +\cdots+\lambda_1\lambda_2^{n-2}+\lambda_2^{n-1}) -\lambda_1\lambda_2(\lambda_1^{n-2}+\lambda_1^{n-3}\lambda_2 +\cdots+\lambda_1\lambda_2^{n-3}+\lambda_2^{n-2}) =(\lambda_1^{n}+\lambda_1^{n-1}\lambda_2+\cdots+\lambda_1^2 \lambda_2^{n-2}+\lambda_1\lambda_2^{n-1}) + (\lambda_1^{n-1}\lambda_2+\lambda_1^{n-2}\lambda_2^2+\cdots +\lambda_1\lambda_2^{n-1}+\lambda_2^{n}) -(\lambda_1^{n-1}\lambda_2+\lambda_1^{n-2}\lambda_2^2+\cdots +\lambda_1\lambda_2^{n-1}+\lambda_2^{n}) =\lambda_1^{n}+\lambda_1^{n-1}\lambda_2+\cdots+\lambda_1^2 \lambda_2^{n-2}+\lambda_1\lambda_2^{n-1} =\sum_{i=1}^{n}\lambda_1^{n+1-i}\lambda_2^{i-1}=k_{n+1}
Next, we prove k_n=\begin{cases}\displaystyle{(\lambda_1^{n}-\lambda_2^{n}) \over (\lambda_1-\lambda_2)}& \mbox{if}\ \lambda_1\neq\lambda_2,\\ n\lambda_1^{n-1} & \mbox{if}\ \lambda_1=\lambda_2.\end{cases}
  • If \lambda_1=\lambda_2
    k_n=\sum_{i=1}^{n}\lambda_1^{n-i}\lambda_1^{i-1}= \sum_{i=1}^{n}\lambda_1^{n-1} = n\cdot\lambda_1^{n-1}
  • If \lambda_1\neq\lambda_2
    (\lambda_1-\lambda_2)k_n=(\lambda_1-\lambda_2)(\lambda_1^{n-1}+\lambda_1^{n-2} \lambda_2 +\cdots+\lambda_1\lambda_2^{n-2}+\lambda_2^{n-1}) = (\lambda_1^{n}+\lambda_1^{n-1}\lambda_2+\cdots+\lambda_1^2 \lambda_2^{n-2}+\lambda_1\lambda_2^{n-1}) - (\lambda_1^{n-1}\lambda_2+\lambda_1^{n-2}\lambda_2^2+\cdots +\lambda_1\lambda_2^{n-1}+\lambda_2^{n}) =\lambda_1^{n}-\lambda_2^{n} \Rightarrow k_n= {(\lambda_1^{n}-\lambda_2^{n}) \over (\lambda_1-\lambda_2)}
Finally, we prove A^n=k_nA-\lambda_1\lambda_2k_{n-1}I_2. By mathematical induction, we have P_1: A=k_1A-\lambda_1\lambda_2 k_0I_2 = A is true. And suppose that P_n: A^n=k_nA-\lambda_1\lambda_2k_{n-1}I_2 is true. Then we have P_{n+1}: A^{n+1} = AA^{n} = k_nA^2-\lambda_1\lambda_2k_{n-1}I_2A From problem 3, we know that A^2=(a+d)A-(ad-bc)I_2. And we have the following conclusion by basic algebra \begin{cases}\lambda_1+\lambda_2=a+d\\ \lambda_1\lambda_2=ad-bc, \end{cases} thus A^{n+1} = k_n[(a+d)A-(ad-bc)I_2]-\lambda_1\lambda_2k_{n-1}A =k_n(\lambda_1+\lambda_2)A-k_n\lambda_1\lambda_2I_2 -\lambda_1\lambda_2k_{n-1}A =[k_n(\lambda_1+\lambda_2)-\lambda_1\lambda_2k_{n-1}]A - k_n\lambda_1\lambda_2I_2 =k_{n+1}A- \lambda_1\lambda_2k_nI_2 which follows the same form of A^n and hence the assumption of P_n is true.

8. Use Question 7 to prove that if A=\begin{bmatrix}1&2\\2&1 \end{bmatrix}, then A^{n}={3^n\over2}\begin{bmatrix}1&1\\1&1 \end{bmatrix}+{(-1)^{n-1}\over2}\begin{bmatrix}-1&1\\1&-1 \end{bmatrix} if n\geq1.

Solution:
\lambda_1 and \lambda_2 are the roots of x^2-x-3=(x-3)(x+1) \Rightarrow \lambda_1=3,\ \lambda_2=1 Note that \lambda_1\neq\lambda_2 and use the formula from the previous problem we have k_n={3^n-(-1)^n\over3-(-1)}={3^n-(-1)^n\over4},\ k_{n-1}={3^{n-1}- (-1)^{n-1}\over4} Hence A^{n}=k_nA-\lambda_1\lambda_2k_{n-1}I_2 ={3^n-(-1)^n\over4}\cdot\begin{bmatrix}1&2\\2&1 \end{bmatrix} +3\cdot{3^{n-1}- (-1)^{n-1}\over4}\cdot\begin{bmatrix}1 & 0\\ 0 & 1 \end{bmatrix} ={3^n + (-1)^{n-1} \over4} \cdot \begin{bmatrix}1&2\\2&1 \end{bmatrix} +{3^{n} - 3\cdot(-1)^{n-1}\over4}\cdot\begin{bmatrix}1 & 0\\ 0 & 1 \end{bmatrix} =\begin{bmatrix}\displaystyle{3^n+(-1)^{n-1} +3^n -3\cdot(-1)^{n-1} \over 4} & \displaystyle{3^n+(-1)^{n-1} \over 2}\\ \displaystyle{3^n+(-1)^{n-1} \over 2} & \displaystyle{3^n+(-1)^{n-1} +3^n -3\cdot(-1)^{n-1} \over 4}\end{bmatrix} =\begin{bmatrix}\displaystyle{3^n\over 2} - {(-1)^{n-1}\over 2} & \displaystyle{3^n\over 2} + {(-1)^{n-1}\over 2}\\ \displaystyle{3^n\over 2} + {(-1)^{n-1}\over 2} & \displaystyle{3^n\over 2} - {(-1)^{n-1}\over 2}\end{bmatrix} = {3^n\over2} \begin{bmatrix}1&1\\1&1 \end{bmatrix} +{(-1)^{n-1}\over2} \begin{bmatrix}-1&1\\1&-1 \end{bmatrix}
9. The Fibonacci numbers are defined by the equations F_0=0, F_1=1 and F_{n+1}=F_n+F_{n-1} if n\geq1. Prove that F_n={1\over\sqrt{5}}\left(\left({1+\sqrt{5}\over2}\right)^n -\left({1-\sqrt{5}\over2}\right)^n\right)
Solution:
Since F_{n+1}=F_n+F_{n-1}, we have \begin{bmatrix}F_{n+1}\\ F_{n} \end{bmatrix}=\begin{bmatrix}1 & 1\\ 1 & 0 \end{bmatrix}\cdot\begin{bmatrix}F_{n}\\ F_{n-1} \end{bmatrix}= A\cdot\begin{bmatrix}F_{n}\\ F_{n-1} \end{bmatrix} = A^{n}\cdot\begin{bmatrix}F_{1}\\ F_{0} \end{bmatrix} = A^{n}\cdot \begin{bmatrix}1 \\ 0 \end{bmatrix} where A = \begin{bmatrix}1 & 1\\ 1 & 0 \end{bmatrix}. From problem 7, we know \lambda_1 and \lambda_2 are the roots of x^2-x-1\Rightarrow \lambda_1={1+\sqrt{5}\over2},\ \lambda_2={1-\sqrt{5}\over2}. And k_n={\lambda_1^n-\lambda_2^n\over\lambda_1-\lambda_2} = {\left({1+\sqrt{5}\over2}\right)^n-\left({1-\sqrt{5}\over2}\right)^n \over\sqrt{5}} \Rightarrow A^{n}=k_nA-\lambda_1\lambda_2k_{n-1}I_2=k_nA+k_{n-1}I_2 Hence \begin{bmatrix}F_{n+1}\\ F_{n} \end{bmatrix} = A^{n}\cdot \begin{bmatrix}1 \\ 0 \end{bmatrix} = (k_nA+k_{n-1}I_2)\cdot \begin{bmatrix}1 \\ 0 \end{bmatrix} = \begin{bmatrix}k_n+k_{n-1} & k_n\\k_n& k_{n-1}\end{bmatrix} \cdot \begin{bmatrix}1 \\ 0 \end{bmatrix}= \begin{bmatrix}k_n+k_{n-1}\\ k_n\end{bmatrix} That is, F_n=k_n = {1 \over\sqrt{5}}\cdot \left(\left({1+\sqrt{5}\over2}\right)^n - \left({1-\sqrt{5}\over2}\right)^n\right)
10. Let r > 1 be an integer. Let a and b be arbitrary positive integers. Sequences x_n and y_n of positive integers are defined in terms of a and b by the recurrence relations x_{n+1}=x_n+ry_n y_{n+1} = x_n + y_n, for n\geq0, where x_0=a and y_0=b.
Use Question 7 to prove that \lim_{n\to\infty}{x_n\over y_n}=\sqrt{r}
Solution:
\begin{bmatrix}x_{n+1}\\ y_{n+1} \end{bmatrix} = \begin{bmatrix}1 & r\\1 & 1 \end{bmatrix} \cdot \begin{bmatrix}x_{n}\\ y_{n} \end{bmatrix} = A\cdot \begin{bmatrix}x_{n}\\ y_{n} \end{bmatrix} = A^{n+1}\cdot \begin{bmatrix}x_{0}\\ y_{0} \end{bmatrix} = A^{n+1}\cdot \begin{bmatrix}a\\ b \end{bmatrix} where A = \begin{bmatrix}1 & r\\1 & 1 \end{bmatrix}.
\lambda_1 and \lambda_2 are the roots of x^2-2x+(1-r), hence \lambda_1=1+\sqrt{r},\ \lambda_2 = 1-\sqrt{r}\Rightarrow k_n={\lambda_1^n-\lambda_2^n\over \lambda_1-\lambda_2} ={\lambda_1^n-\lambda_2^n\over 2\sqrt{r}} And A^{n} = k_nA-\lambda_1\lambda_2k_{n-1}I_2 = k_nA-(1-r)k_{n-1}I_2 \Rightarrow \begin{bmatrix}x_{n}\\ y_{n} \end{bmatrix} = (k_nA-(1-r)k_{n-1}I_2)\cdot \begin{bmatrix}a\\ b \end{bmatrix} =\left(\begin{bmatrix}k_n & rk_n\\k_n & k_n \end{bmatrix}-\begin{bmatrix}(1-r)k_{n-1} & 0\\0 & (1-r)k_{n-1} \end{bmatrix}\right) \cdot \begin{bmatrix}a\\ b \end{bmatrix} = \begin{bmatrix}k_n-(1-r)k_{n-1} & rk_n\\k_n & k_n-(1-r)k_{n-1} \end{bmatrix}\cdot \begin{bmatrix}a\\ b \end{bmatrix} =\begin{bmatrix}a(k_n-(1-r)k_{n-1}) + brk_n\\ ak_n + b(k_n-(1-r)k_{n-1}) \end{bmatrix} Since \lim_{n\to\infty}{k_n\over k_{n-1}}=\lim_{n\to\infty}{\lambda_1^{n}-\lambda_2^{n}\over \lambda_1^{n-1}-\lambda_2^{n-1}} = \lim_{n\to\infty} {\lambda_1^n\left(1-\left(\displaystyle{\lambda_2\over\lambda_1} \right)^n\right) \over \lambda_1^{n-1}\left(1-\left(\displaystyle {\lambda_2\over\lambda_1} \right)^{n-1}\right)} = \lambda_1 = 1+\sqrt{r} Thus \lim_{n\to\infty}{x_n\over y_n}=\lim_{n\to\infty} {a(k_n-(1-r)k_{n-1}) + brk_n \over ak_n + b(k_n-(1-r)k_{n-1})} =\lim_{n\to\infty} {a(1+\sqrt{r}-(1-r))+br(1+\sqrt{r}) \over a(1+\sqrt{r}) + b(1+\sqrt{r}-(1-r))} =\lim_{n\to\infty} {a(\sqrt{r} + r) + br(1+\sqrt{r}) \over a(1+\sqrt{r}) + b(\sqrt{r}+r)} =\lim_{n\to\infty}{\sqrt{r}[a(1+\sqrt{r}) + b(\sqrt{r}+r)] \over a(1+\sqrt{r}) + b(\sqrt{r}+r)} = \sqrt{r}





没有评论:

发表评论